Activities and Ergonomics of Workers in Broiler Hatcheries - CCS Carvalho; C de F Souza; I de FF Tinôco; LV Santos; LJ Minette; EP da Silva (Brazilian Journal of Poultry Science, 2015)
The objective this study was to assess ergonomic factors, posture and biomechanics of workers of a broiler egg hatchery. The analysis of ergonomic factors was based on physical work load, thermal environment, and exposure to light and noise. The posture of workers was analyzed using photographic records which were evaluated by the software program OWAS (Ovako Working Posture Analysing System). A biomechanics analysis was also performed based on the photographs taken of the employee at various angles, which were used as inputs to the Michigan two-dimensional biomechanical model software program. The results show that certain activities can be considered unhealthy due to the exposure of employees to physical and thermal overload. The continuous noise levels and lighting were outside the range considered adequate by the regulations of the Brazilian Ministry of Labor. The manner in which certain activities are carried out when associated with weight and poor posture can result in body lesions in broiler hatchery employees. It is therefore necessary to apply specific ergonomic programs, including scheduled breaks, training, and other measures in order to reduce or to eliminate the risks involved in these activities.